Influence of Brooder Diet and Seasonal Temperature on Reproductive Efficiency of Clownfish Amphiprion sebae in Captivity - T.T. Ajith Kumar1, R. Vinoth1 and T. Shunmugaraj2, K.V. Dhaneesh1 (Recent Research in Science and Technology, 2011)
An attempt was made to study the influence of seasonal temperature and different feed (boiled clam meat, trash fish, live Acetes sp. and formulated feed) on reproductive efficiency of the clownfish Amphiprion sebae in captivity using brackish water. The fishes were segregated as two groups and accommodated in separate tanks as pairs. First group fed with different feeds for evaluating their breeding efficiency and second group is to find the influence of surrounding temperature on their reproduction. A. sebae spawned at regular interval in relation to seasonal temperature and higher spawning frequency (2.67 times month-1) was observed in summer and spring months (28.7±0.72ºC). Spawning frequency was found low (2 times month-1) during winter (25.3±0.76 ºC). Higher reproductive efficiency [number of eggs laid (260±14.6 eggs nest-1)] was observed when they had fed live Acetes spp than other feeds such as clam meat (196±12.9 eggs nest-1), trash fish (151±8.9 eggs nest-1) and formulated feed (105±6.9 eggs nest-1). According to the present study, it is revealed that, the maximum number of spawning was observed in the summer and spring months and the brooder fishes showed higher reproductive efficiency, when they fed with live Acetes sp.